Self-resilience as a protective factor against development of post-traumatic stress disorder symptoms in police officers - Lee, Jong-Ku; Choi, Hyeon-Gyeong; Kim, Jae-Yeop; Nam, Juhyun; Kang, Hee-Tae; Koh, Sang-Baek; Oh, Sung-Soo (Annals of occupational and environmental medicine, 2016)
Background This study was conducted to check whether self-resilience, one of the characteristics known to affect the occurrence of post-traumatic stress disorder (PTSD) symptoms after experiencing traumatic events, could serve as a protective factor for police officers whose occupational factors are corrected. Methods We conducted a cross-sectional study in which 112 male police officers in Gangwon Province participated. They visited the Wonju Severance Christian Hospital Occupational Environment Center for medical check-ups from June to December 2015. Their general characteristics were identified using structured questionnaires, and they were asked to fill in the Korean Occupational Stress Scale-Short Form (KOSS-SF). Further, the Center for Epidemiologic Studies-Depression Scale (CES-D), Connor–Davidson Resilience Scale-Korean (CD-RI-K), and Impact of Event Scale-Revised-Korean version (IES-R-K) were used to evaluate their job stress, depression, self-resilience, and PTSD symptoms. Logistic regression analysis was conducted to correct their personal, occupational, and psychological factors to analyze the relationship between self-resilience and PTSD symptoms. Results Among 112 respondents who experienced a traumatic event, those with low self-resilience had significantly higher rate of PTSD symptoms than those with high self-resilience even after correcting for the covariate of general, occupational, and psychological characteristics (odds ratio [OR] 3.51; 95 % CI: 1.06–19.23). Conclusions Despite several limitations, these results suggest that a high degree of self-resilience may protect police officers from critical incident-related PTSD symptoms.